A newborn with anaphylaxis due to vancomycin - Aydın, Banu; Botan, Edin (The Turkish Journal of Pediatrics, 2022)
Background. All drugs may cause hypersensitivity reactions. Anaphylaxis is a medical emergency that rarely occurs in newborns due to immature immunity. Early diagnosis and treatment are life-saving. Vancomycin, a glycopeptide antibiotic with bactericidal action against Gram-positive bacteria, is commonly used for neonatal nosocomial sepsis. Case. We hereby present a premature infant (born at the 33rd week of gestation, birth weight: 1745 grams) who was started on vancomycin on postnatal day 7. He had severe circulatory failure and stridor during infusion on day 7 of vancomycin treatment and his tryptase level was elevated to 64.60 micrograms/L Conclusions. To the best of our knowledge, there is no neonatal case of anaphylaxis due to vancomycin in the literature. Neonatologists should keep in mind that an anaphylactic reaction with a fatal course may develop during vancomycin infusion.
Keywords: anaphylaxis; newborn; vancomycin